Fulminant Acute Postoperative Endophthalmitis caused by Pseudomonas stutzeri in a Healthy Elderly Male - George Michael N. Sosuan, MD; Kevin Kenjee K. Dee, MD; Jomel G. Lapides, MD; Ruben Lim Bon Siong, MD (Philippine Journal of Ophthalmology, 2024)
Objective: To report a case of acute postoperative endophthalmitis following cataract surgery due to Pseudomonas stutzeri in a healthy elderly male.